Policy Change Implication Toward Integrated Wonorejo Zone as A Strategic Economic Development Zone - Akbar Pandu Dwinugraha; Mardiono Mardiono; Sarwono Sarwono (Program Pascasarjana, 2014)
Integrated Wonorejo Zone is one of the development zone in Lumajang Regency with significant goals to improve potensial condition in three aspect namely tourism, agriculture and SMEs. Based on RTRW in 2008-2028, which was established in 2008, the development strategy of this zone is change. Integrated Wonorejo Zone was mentioned as a Strategic Economic Development Zone. This research describe and analyse about how the implication of policy change toward Integrated Wonorejo Zone. This research using method of descriptive research with qualitative approach as well as analysis of data by John Seidel about QDA (qualitative data analysis). The result of this research explain that the policy change implication, from description, implementation and implication point of view did not give significant expectation. Key Words: Policy Change, Integrated Wonorejo Zone, Strategic Economic Development Zone.